In Silico Antiosteoporosis Activity of 96% Ethanol Extract of Chrysophyllum cainito L. Leaves - Ma’arif, Burhan; Muslikh, Faisal Akhmal; Najib, Luqman Alfani; Atmaja, Ria Ramadhani Dwi; Dianti, Meilina Ratna (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v1i0.1460, 2021)
Estrogen deficiency causes various health problems in postmenopausal women, including osteoporosis. Phytoestrogens are emerging as potential estrogen alternatives with minimal side effects. This study aimed to predict the antiosteoporosis activity of the compounds from 96% ethanol extract of Chyrsophyllum cainito L. leaves through in silico study on 3OLS protein, an X-ray protein of ERβ. In silico analysis was carried out on the compounds from metabolite profiling results of 96% ethanol extract of C. cainito leaves from previous studies. The structure of compounds resulting from metabolite profiling of 96% ethanol extract of C. cainito leaves was made using Avogadro 1.0.1 software, geometry optimization with Chemdraw molecular docking was carried out using PyRx 0.8 software, and Biovia Discovery Studio Visualizer 2021 software was used to visualize the structure of compounds against 3OLS proteins. The physicochemical characteristics of the compounds were analyzed using the SwissADME webtool. From the result, it was known that there were seven compounds in the leaves of C. cainito, which were suspected to be phytoestrogens that had ERβ agonist properties against 3OLS protein. It was an ERβ agonist because the compound had similar parameters to 17β-estradiol in its interaction with the 3OLS protein, which had a pharmacophore distance of about 10,862, and bound to the amino acids His 475 and Glu 305 or Arg 346. The 96% ethanol extract of C. cainito leaves contained seven compounds thought to be phytoestrogen with an ERβ agonist that handled its antiosteoporosis activity.